(3geY GdghGeY aj TQM LeY GdLhGeYs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3JGL GdOjf GdSHcj , CHh fUQ,J (B771 (3g` s ((3YHOGdQGRb Hf YHGS GdYjGOj GdTGaYj s)
(3ChdgG (B:s
(3hHYO, aEf dfG JCdjakG aj GdYQHjI LeY COfGgG hCbUGgG hLeYJg ef fMh eFI eUfa s
(3BNQgG (B:s
(3aOhfc eNJUQG GfWhi Ydi RHOI eFI eUfa hCJi ef GdYLH GdYLGH HeG de jLeYg bHdg eDda gcPG HCUd GdeDda QMeg Gddg s
(3fSNI KGfjI JJab aj ChdgG eY GdfSNI GdChdi JeGekGs
(3haj BNQgG HGNJdGa jSjQ aj HYV GdCdaGXs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs